PENGEMBANGAN MODUL ANTI NARKOBA - Verawati, Verawati; Harapan, Edi; Fitria, Happy (Graduate Program Magister Manajemen Pendidikan, 2021)
This study determined the development of modules as teaching materials for Anti Narcotics learning, to find out the quality of modules in learning Anti Narcotics in terms of content eligibility, language feasibility, presentation, and images, as well as to determine the effectiveness of the use of teaching materials in the form of modules learning in Anti Narcotics. This study uses the Dick and Carey development model. The module feasibility test is carried out by means of product feasibility testing by reviewing trial design and review design and then given an observation sheet (walkthrough sheet) covering the suitability of content, media, and language by media experts, material experts, and linguists. The subjects of the trial were students of SMP Negeri 1 Indralaya Selatan through three stages: individual trials taken by 3 random students, small group trials consisting of 10 students, and field trials consisting of 28 students. The results of research and development of Anti Narcotics module produles namely the quality of the modules developed are valid according to material experts, media experts, and linguists. The Anti Narcotics Module is feasible and effective to be used by students during field trials and is able to assist students in learning drug material. This research is expected to be used as a reference for developing modules on other materials.